1985
DOI: 10.3171/jns.1985.62.6.0823
|View full text |Cite
|
Sign up to set email alerts
|

Supraophthalmic carotid infusion for brain chemotherapy

Abstract: A single-lumen catheter with a maneuverable tip which does not incorporate a balloon has been developed for supraophthalmic intracarotid infusion of chemotherapeutic agents for central nervous system neoplasms. Supraophthalmic carotid catheterization was accomplished in 48 (96%) of the first 50 consecutive infusions in which this catheter was used. None of the 31 patients who underwent this procedure developed optic neuropathy or loss of vision. Ten patients developed Marcus-Gunn pupils, ipsilateral to the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In clinical practice, the tip of a superselective catheter is usually placed in the A1 segment of the anterior cerebral artery, the M1 segment of the middle cerebral artery, or in the posterior communicating artery (182). Supraophthalmic carotid infusion became the preferred procedure to prevent drugs from entering the eye (184,(186)(187)(188)(189)(190)(191). Flow-directed soft-tipped balloon or singlelumen catheters (188) with an extended tip (182-184) can be remotely controlled by hydraulic forces (189) and allow to maneuver even in extremely curved skull base vessels (184).…”
Section: Siacimentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, the tip of a superselective catheter is usually placed in the A1 segment of the anterior cerebral artery, the M1 segment of the middle cerebral artery, or in the posterior communicating artery (182). Supraophthalmic carotid infusion became the preferred procedure to prevent drugs from entering the eye (184,(186)(187)(188)(189)(190)(191). Flow-directed soft-tipped balloon or singlelumen catheters (188) with an extended tip (182-184) can be remotely controlled by hydraulic forces (189) and allow to maneuver even in extremely curved skull base vessels (184).…”
Section: Siacimentioning
confidence: 99%
“…Supraophthalmic carotid infusion became the preferred procedure to prevent drugs from entering the eye (184,(186)(187)(188)(189)(190)(191). Flow-directed soft-tipped balloon or singlelumen catheters (188) with an extended tip (182-184) can be remotely controlled by hydraulic forces (189) and allow to maneuver even in extremely curved skull base vessels (184). It has been reported that supraophthalmic carotid chemotherapy can be used to treat malignant gliomas with low dose cisplatin and BCNU (182,191,192), and that the pharmacokinetic changes of 11 C-BCNU are consistent with the metabolic changes captured by PET (185).…”
Section: Siacimentioning
confidence: 99%
“…Intermittent infusion of chemother apeutic drugs into the carotid artery has long been used as an experimental approach to the treatment of brain tumors. The drug most commonly infused into the carotid artery is 1,3-bis-chloroethylni trosourea (BCNU) (Greenberg et al, 1984;Hoch berg et al, 1985;Kapp et al, 1985). Our group is conducting a trial of continuous infusion of the ra diosensitizing drug 5' -bromodeoxyuridine (BUdR) for malignant gliomas (Greenberg et al, 1988).…”
mentioning
confidence: 99%